EFL learners' lexical availability: Exploring frequency, exposure, and vocabulary level. (July 2020) - Akbarian, Is'haaq; Farajollahi, Fatemeh; Jiménez Catalán, Rosa María
Abstract: Lexical availability studies have a great potential to explore and contribute to a better understanding of productive vocabulary knowledge in a second or foreign language. The present study compared the lexical availability output of two groups of EFL learners in order to ascertain whether the different prompts used in the lexical availability task or the different amount of English exposure had any quantitative or qualitative effect on learners' lexical availability output. The study also aimed at determining if there was a relationship between receptive vocabulary knowledge and lexical availability output. A sample of 85 EFL learners, distributed into incoming and outgoing groups, completed a lexical availability task and the New Vocabulary Levels Test (NVLT). Results showed that the prompt and the amount of English instruction influenced the number and quality of learners' word responses. There was also a positive, although moderate, correlation between the scores on lexical availability task and NVLT, predicting vocabulary level to some extent.